2005
DOI: 10.1007/s10238-004-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid metabolism in women with age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is one of the leading causes of visual loss among people aged 65 and older. At present the origin of AMD still remains unknown. The objective was to evaluate the chosen lipid and lipoprotein concentrations in blood of patients with AMD. Sixty women aged 55-71 (mean age 65.1+/-5.7) were treated in the outpatient ophthalmological clinic for more than two years because of AMD. We evaluated total serum cholesterol (TCH), triglycerides (TG), HDL-cholesterol (HDL), LDL-choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 30 publications
3
42
1
1
Order By: Relevance
“…Data regarding the association between serum HDL levels and AMD are conflicting (37,(39)(40)(41)(42)(43)(44). Some studies found no relationship (37,43), whereas others found that increased risk of AMD or a subphenotype was associated with increased HDL levels (39,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding the association between serum HDL levels and AMD are conflicting (37,(39)(40)(41)(42)(43)(44). Some studies found no relationship (37,43), whereas others found that increased risk of AMD or a subphenotype was associated with increased HDL levels (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found no relationship (37,43), whereas others found that increased risk of AMD or a subphenotype was associated with increased HDL levels (39,41). Three studies have shown an inverse relationship with either decreased HDL levels in AMD cases or decreased incidence of advanced AMD with higher HDL (40,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have not found an association between serum lipid profile and AMD risk [18,20,23]. Elevated HDL but not total cholesterol was associated with an increased risk of AMD in a study by Van Leeuwen et al [18] Non neovascular AMD was unrelated to cholesterol level in a study by Hyman et al [20] No difference in total cholesterol, triglycerides, phospholipids, HDL, LDL concentrations were observed between AMD patients and controls in the study by Abalain et al [23], and there was no significant difference in the concentration of the Lipoprotein(a) between the AMD and control groups in the work by Nowak et al [24].…”
Section: Lipids and Amdmentioning
confidence: 95%
“…To date, epidemiological studies on the association between serum lipid and AMD risk have been inconsistent [18][19][20][21][22][23][24][25][26]. Part of this variability may have resulted from reporting different forms and stages of AMD with different lipid profiles.…”
Section: Lipids and Amdmentioning
confidence: 99%
“…Ha alaposan elemezzük az AMD kockázati tényezőinek tekintett állapotokat (1. táblázat) -ezek közé tartozik az AMD családi halmozódása [24], az öregedés/öregség [25], az AMD-re hajlamosító, komplementtel kapcsolatos genetikai polimorfi zmus [26], a dohányzás [27], az elhízás, illetve a kórosan nagyobb testtömegindex [27], a hypertonia, magasabb szisztolés-diasztolés és átlagos artériás vérnyomás [27], a praeeclampsia [28], a fi brinogén emelkedett szintje [29], a hypercholesterinaemia (emelkedett összes koleszterin) és az étkezés utáni hyperlipaemia [29], koleszterinben dús étrend [30], magas zsírbevitellel járó táplálkozás [31], disznózsír és szilárd zsírok (szilárd növényi olaj) és szilárd zsírral sütött ételek (a szérumkoleszterin-szinttől, illetve testtömegindextől függetlenül) [32], magas LDL-koleszterin-szint [29] (a HDL-koleszterin emelkedett, szívvédő hatásúnak tekintett koncentrációszintje az AMD csökkent kockázatával jár), csökkent HDL-koleszterin [32], a trigliceridek felszaporodása [32], az ApoB emelkedett és az ApoA csök-kent koncentrációja [32], magas oxidált LDL-koleszterin-szint [33], megnőtt ApoA1- [34], magas szérumfi brinogén-szint [27], emelkedett CRP [35], magas interleukin-6 [36], az intracelluláris adhéziós mole- ÖSSZEFOGLALÓ KÖZLEMÉNY kula magas szérumszintje [36,37], emelkedett von Willebrand-faktor [4], magas antifoszfolipidantitest-szint [38], alkoholizmus [39], diabetes mellitus [40,41], ét-kezés utáni hyperglykaemia, illetve nagy glykaemiás indexű táplálék [42], fokozott (szisztémás) AGE-felhalmozódás [43], megnőtt leptin- [44] és csökkent adiponektinszint [44], hypomagnesaemia [45], a cink alacsony szérumszintje [46], metabolikus szindró...…”
Section: Kockázati Tényezők Szerepe Az Időskori Maculadegeneráció Patunclassified